Aksi Bersih-bersih Lingkungan Kampus UNSURI Surabaya dan Perbaikan Saluran Air sebagai Upaya Pencegahan Demam Berdarah - Samuji Samuji; Muhamad Reza Muhaimin; Rahayu Mardikaningsih; Fayola Issalillah; Yeni Vitrianingsih (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Dengue Hemorrhagic Fever (DHF) is a public health issue closely linked to environmental sanitation conditions, including within university settings. Accumulated waste, clogged drainage channels, and stagnant water pools can serve as breeding grounds for Aedes aegypti, the vector that transmits DHF. This community service initiative aimed to improve the quality of the campus environment as a preventive measure against DHF at Universitas Sunan Giri Surabaya. The project employed the Asset-Based Community Development (ABCD) method following the stages of discovery, dream, design, and destiny and involved students, faculty members, and the broader academic community. Activities included environmental assessments, coordination and task allocation, a collaborative campus cleanup drive, drainage channel cleaning and restoration, weed removal, and educational outreach regarding the importance of environmental hygiene in preventing DHF. Evaluations were conducted through pre- and post-activity observations focusing on environmental cleanliness, drainage functionality, and participant engagement. The results demonstrated a cleaner campus environment, restored drainage functionality (thereby reducing the risk of stagnant water), and increased participation and awareness among the academic community regarding environmental maintenance. This initiative highlights the effectiveness of the ABCD approach in leveraging the potential and collaborative spirit of the academic community to create a clean, healthy campus environment that supports sustainable DHF prevention efforts.